Microfinance in marginal and upland areas - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1999)
Microfinance comprises microsavings, microcredit and other financial services such as microinsurance and microleasing. Small amounts of savings are col-lected: daily, weekly, at market days, after harvests or irregularly. They are then transformed into microloans which are repaid in microinstalments: this is micro-credit. I call any institution that provides such microfinancial services a microfi-nance institution. This includes financial self-help groups, savings and credit co-operatives, rural banks, branches of Agricultural Development Banks and some commercial banks, furthermore moneylenders, deposit collectors, credit NGOs and rotating savings and credit associations. A small number of them is donor-supported. Sustainable rural financial institutions are a prerequisite of sustain-able rural development in any country and any region.
Keywords: 330